Successful Case-based Reasoning Applications-2 - Montani, Stefania; Jain, Lakhmi C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Case-based reasoning paradigms offer automatic reasoning capabilities which are useful for the implementation of human like machines in a limited sense. This research book is the second volume in a series devoted to presenting Case-based reasoning (CBR) applications. The first volume, published in 2010, testified the flexibility of CBR, and its applicability in all those fields where experiential knowledge is available. This second volume further witnesses the heterogeneity of the domains in which CBR can be exploited, but also reveals some common directions that are clearly emerging in recent years. This book will prove useful to the application engineers, scientists, professors and students who wish to develop successful case-based reasoning applications.
Cased -Based Reasoning Systems -- A Study of Two-Phase Retrieval for Process-Oriented Case-Based Reasoning -- Evaluating a Case-based Reasoning Architecture for the Intelligent Monitoring of Business Workflows -- The COLIBRI platform: Tools, features and working examples.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).